Copper slag self-pulverization iron extraction method and application thereof

By mixing the copper slag with calcium oxide-based additives, heating and cooling to form self-powdered copper slag, and magnetic separation, the problems of high energy consumption and long production lines in the copper slag treatment in the prior art are solved, and efficient iron recovery and particle size control are achieved.

CN119571049APending Publication Date: 2025-03-07CENT SOUTH UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411690299.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the existing copper slag treatment process, crushing and grinding are required, resulting in high energy consumption and long production lines, and the inability to effectively utilize the iron resources in copper slag.

Method used

By mixing the copper slag with calcium oxide-based additives, heating to 1250°C to 1700°C, insulated and cooled slowly to form self-powdered copper slag, and magnetite is recovered by magnetic separation.

Benefits of technology

The self-powdering and iron extraction of copper slag is realized, which reduces the crushing and grinding steps, reduces energy consumption, improves the iron recovery rate, and meets the particle size requirements of less than 200 mesh of magnetic separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571049A_ABST
    Figure CN119571049A_ABST
Patent Text Reader

Abstract

The invention provides a copper slag self-pulverization iron extraction method and application thereof.The copper slag self-pulverization iron extraction method comprises the steps that copper slag and a calcium oxide-based additive are mixed to obtain mixed copper slag, the calcium oxide-based additive comprises calcium oxide and / or a calcium oxide raw material, the calcium oxide raw material can generate calcium oxide through heating, and the calcium oxide raw material can generate calcium oxide through heating; the adding amount of the calcium oxide-based additive meets the condition that the total mass of the primary calcium oxide and / or the generated calcium oxide is 29%-47% of the mass of fayalite in the copper slag; after the mixed copper slag is heated to 1250-1700 DEG C, heat preservation is conducted for 30-120 min, and modified copper slag is obtained; slowly cooling the modified copper slag at a cooling rate of 0.25-1 DEG C / min to obtain self-pulverization copper slag; and magnetic separation is performed on the self-pulverization copper slag, magnetite is recycled, and the technical problems of tedious production line and high energy consumption caused by the fact that procedures such as crushing and ore grinding cannot be avoided in the common technology are ingeniously solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of copper slag treatment, and particularly relates to a method for extracting iron by self-pulverization of copper slag and application thereof. Background Art

[0002] In the copper production process, an average of 2.2 tons of copper slag is produced for every ton of copper produced. Copper slag is difficult to dispose of, and the accumulated copper slag over the years is conservatively estimated to have exceeded 100 million tons, occupying a large amount of land resources, causing serious secondary pollution of heavy metals and waste of resources. In fact, copper slag is rich in iron, so it is crucial to properly treat copper slag and fully utilize the iron resources in copper slag.

[0003] The copper slag treatment process in common technology often adopts grinding and flotation to extract copper and magnetic separation to extract iron. The above processes of extracting and separating valuable components in copper slag require crushing and grinding. The energy consumption of crushing and grinding generally accounts for more than 90% of the energy consumption of the entire grinding and flotation process. From the perspective of energy utilization, grinding itself is a means with very low cost performance.

[0004] In view of this, it is necessary to provide a method for self-pulverization of copper slag to extract iron, so as to alleviate or solve the above problems. Summary of the invention

[0005] In order to solve the technical problem that the above-mentioned conventional technology cannot avoid the processes of crushing and grinding in the process of extracting iron from copper slag, resulting in a long production line and high energy consumption, the present invention provides a method for extracting iron from copper slag by self-pulverization, comprising the steps of:

[0006] Mixing copper slag and a calcium oxide-based additive to obtain a mixed copper slag, wherein the calcium oxide-based additive includes calcium oxide and / or the calcium oxide raw material, the calcium oxide raw material can generate calcium oxide by heating, and the amount of the calcium oxide-based additive added satisfies that the total mass of the native calcium oxide and / or the generated calcium oxide is 29% to 47% of the mass of the fayalite phase in the copper slag;

[0007] The mixed copper slag is heated to 1250° C. to 1700° C. and kept warm for 30 to 120 minutes to obtain modified copper slag;

[0008] The modified copper slag is slowly cooled to room temperature at a cooling rate of 0.25 to 10 (including 0.5 and 1)°C / min to obtain the pulverized copper slag;

[0009] The self-pulverized copper slag is subjected to magnetic separation to recover magnetite.

[0010] Furthermore, in terms of mass fraction, the mass proportion of the fayalite phase in the copper slag is 10% to 40%.

[0011] Furthermore, the particle size of the self-pulverizing copper slag is 1 to 100 microns.

[0012] Furthermore, the particle size of the self-pulverizing copper slag is 1-60 um, wherein 90% of the copper slag particle size is concentrated below 30 um.

[0013] Furthermore, the modified copper slag comprises magnetite and β-dicalcium silicate.

[0014] Furthermore, the self-pulverizing copper slag comprises magnetite and gamma-dicalcium silicate.

[0015] Furthermore, the calcium oxide raw material includes calcium carbonate and / or calcium sulfate.

[0016] Furthermore, when the calcium oxide-based additive is calcium oxide, the heating temperature is 1400-1700°C; when the calcium oxide-based additive is calcium carbonate / calcium sulfate, the heating temperature is 1250-1700°C.

[0017] Furthermore, in the step of magnetically separating the self-pulverized copper slag to recover magnetite, the magnetic field intensity of the magnetic separation is 0.05-0.10T.

[0018] The present invention also provides an application of the method for extracting iron by self-pulverization of copper slag as described in any one of the above items in copper slag treatment.

[0019] Compared with the prior art, the present invention has at least the following advantages:

[0020] like Figure 1 As shown, the present invention limits the amount of calcium oxide in the calcium oxide-based additive to 5% to 9% of the mass of the copper slag, so that the composition point of the mixed copper slag is adjusted to the C2S primary crystallization zone in the CaO-FeO-SiO2 phase diagram, the liquidus iron content is controlled to be above 90%, and the iron element is enriched in the liquid phase. The iron recovery rate can reach more than 90%, thereby achieving a stable improvement in the iron recovery rate from the source.

[0021] Based on the control of the composition point of the mixed copper slag, the coordinated heating temperature (1250℃~1700℃) and the cooling rate are limited, so that β-C2S undergoes solid phase transformation during the slow cooling of the mixed copper slag and transforms into γ-C2S. At the same time, the volume expands by about 10%. The internal stress during the volume expansion causes the copper slag to automatically pulverize. Figure 2 , Figure 3As shown in the figure, the particle size of the self-pulverized copper slag is concentrated below 30 microns, which fully meets the particle size requirement of magnetite magnetic separation below 200 mesh (74um), and achieves more thorough monomer dissociation, cleverly solving the technical problem that the crushing, grinding and other processes cannot be avoided in the common technology, resulting in long production lines and high energy consumption. In comparison, the copper slag after slow cooling in the common technology needs to be ground and crushed before it can reach the particle size threshold of 200 mesh for magnetic separation; firstly, the grinding and grinding steps have high energy consumption and low energy utilization, resulting in long production lines and high costs; secondly, the grinding products of the 200 mesh particle size level sometimes cannot achieve monomer dissociation, and some copper plants will grind to 325 mesh. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0023] Figure 1 The CaO-FeO-SiO2 ternary phase diagram used in one embodiment of the present invention, wherein the ① region is the FeO primary crystal region, and the ② region is the dicalcium silicate primary crystal region;

[0024] Figure 2 This is a physical picture of the self-pulverizing copper slag prepared in Example 1 of the present invention;

[0025] Figure 3 : is a particle size distribution diagram of the self-pulverized copper slag prepared in Example 1 of the present invention;

[0026] Figure 4 This is a schematic diagram of using calcium oxide as a raw material to generate a dense C2S shell layer, thereby blocking the reaction in an embodiment of the present invention;

[0027] Figure 5 The figure is a schematic diagram of the process of extracting iron from copper slag by self-pulverization in one embodiment of the present invention. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0030] When numerical ranges are given in the embodiments, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any method, device and material of the prior art similar or equivalent to the method, device and material in the embodiments of the present invention can also be used to implement the present invention.

[0031] like Figure 5 As shown, the present invention provides a method for extracting iron by self-pulverization of copper slag, comprising the steps of:

[0032] S1. Mixing copper slag and a calcium oxide-based additive to obtain a mixed copper slag, wherein the calcium oxide-based additive includes calcium oxide and / or the calcium oxide raw material, the calcium oxide raw material can generate calcium oxide by heating, and the amount of the calcium oxide-based additive added satisfies: the total mass of the native calcium oxide and / or the generated calcium oxide is 29% to 47% of the mass of the fayalite in the copper slag.

[0033] The native calcium oxide is the calcium oxide included in the calcium oxide-based additive, and the generated calcium oxide is the calcium oxide that can be generated by heating the calcium oxide raw material.

[0034] Herein, heating generation refers to that the calcium oxide raw material is heated to a certain temperature to release carbon dioxide and / or sulfur dioxide to generate calcium oxide.

[0035] In some embodiments, the copper slag may be copper smelting slag and copper tailings slag, and the composition of the copper slag includes: 10% to 40% of fayalite.

[0036] Calcium oxide-based additives are chemical reagents that exist stably in the form of calcium oxide under heating conditions. Their types may include calcium oxide, calcium carbonate, and calcium sulfate. Calcium oxide can react with silicon dioxide in the slag to effectively destroy the fayalite phase, reduce fayalite formation, and promote the transformation of the fayalite phase in the slag.

[0037] like Figure 1As shown, the present invention limits the amount of calcium oxide in the calcium oxide-based additive to 29% to 47% of the mass of fayalite in the copper slag, so that the composition point of the mixed copper slag is adjusted to the C2S primary crystallization zone in the CaO-FeO-SiO2 phase diagram, the liquidus iron content is controlled to be above 90%, the iron element is enriched in the liquid phase, the iron recovery rate can reach more than 90%, and the iron recovery rate is steadily improved from the source.

[0038] Exemplarily, the amount of calcium oxide in the calcium oxide additive can be 30% to 32% of the mass of fayalite in the copper slag, such as 35% to 40%, 42% to 43%; in some specific embodiments, the amount of calcium oxide in the calcium oxide additive can be 30% to 32%; in some more specific embodiments, the amount of calcium oxide in the calcium oxide additive can be 42% to 45%.

[0039] In comparison, in the commonly used technology, the composition points of copper slag after adjustment are mostly concentrated in the primary crystal region of FeO in the CaO-FeO-SiO2 phase diagram, such as Figure 1 As shown in area ① in the figure, the liquidus content of iron in the primary crystallization zone is relatively low, and most of the iron will still precipitate out as a silicate mineral phase together with calcium, silicon and oxygen, reducing the iron recovery rate.

[0040] S2. After heating the mixed copper slag to 1250° C. to 1700° C., heat it for 30 to 120 minutes to obtain modified copper slag.

[0041] In step S2, the mixed copper slag is heated to achieve the mineral phase transformation of the mixed copper slag. During the mineral phase reconstruction, the reaction between calcium oxide and silicon dioxide in the copper slag effectively destroys the fayalite phase, reduces the formation of fayalite, promotes the transformation of the fayalite phase in the slag, and promotes the formation of magnetite to obtain the magnetite phase and β-C2S. In the subsequent heat preservation process, the components in the copper slag can be more fully mixed and diffused, and sufficient heat preservation time can ensure that the components in the copper slag have enough time to react and reconstruct, thereby forming stable crystals.

[0042] However, the applicant found that Figure 4 As shown, when the composition point of copper slag is controlled in the C2S primary crystallization zone, the mixed copper slag of this composition will form a dense high-melting-point dicalcium silicate shell layer during the mineral phase reconstruction process, which will cover the surface of calcium oxide and thereby inhibit the reaction process of calcium oxide.

[0043] In view of this, when the calcium oxide additive is calcium carbonate and / or calcium sulfate, the temperature of mineral phase reconstruction can be 1250-1400°C, because:

[0044] CaCO3→CaO+CO2 (the CO2 produced by the reaction can break the dense C2S shell and reduce the reaction temperature, otherwise the shell needs to be dissolved by heating)

[0045] CaSO4→CaO+SO2 (SO2 produced by the reaction can break up the dense C2S shell and reduce the reaction temperature, otherwise the shell needs to be dissolved by increasing the temperature)

[0046] In some embodiments, when the calcium oxide additive is calcium carbonate and / or calcium sulfate, the temperature of the mineral phase reconstruction may be 1250-1700°C. ; In some specific embodiments, the temperature of mineral phase reconstruction may be 1250-1600°C; in some more specific embodiments, the temperature of mineral phase reconstruction may be 1300-1600°C.

[0047] It should be noted that copper slag usually leaves the smelting system at a temperature of about 1250°C.

[0048] Calcium carbonate and calcium sulfate absorb heat and decompose in a high temperature environment. The generated carbon dioxide or sulfur dioxide gas can destroy the dicalcium silicate shell, fully exposing calcium oxide, and the reaction between calcium oxide and silicon dioxide can proceed.

[0049] When the calcium oxide-based additive is calcium oxide, the temperature of mineral phase reconstruction can be adjusted to 1400-1700°C. The dicalcium silicate shell melts at this temperature, which ensures the full reaction of calcium oxide and silicon dioxide and provides the necessary energy and kinetic conditions for the subsequent precipitation and crystallization of β-dicalcium silicate.

[0050] The present invention achieves stable optimization of iron recovery rate by synergistically adjusting the type of calcium oxide-based additives and the temperature of mineral phase reconstruction. In comparison, in the conventional technology, only monocalcium silicate will be generated in the copper slag falling into the FeO primary crystallization zone. The density of monocalcium silicate is low and it will not form a dense shell. Therefore, it will not face the technical problem of dicalcium silicate shell coating in the present application, and there is no motivation to adjust the type of calcium oxide-based additives and the temperature of mineral phase reconstruction.

[0051] The composition of the modified copper slag includes magnetite and β-dicalcium silicate.

[0052] S3. The modified copper slag is slowly cooled at a cooling rate of 0.25°C to 1°C to obtain the pulverized copper slag.

[0053] Based on the control of the composition point of the mixed copper slag, the coordinated heating temperature (1250℃~1700℃) and the cooling rate are limited, so that β-C2S undergoes a solid phase change during the slow cooling process of the mixed copper slag (between 400℃ and 700℃) and transforms into γ-C2S. At the same time, the volume expands by about 10%. The internal stress during the volume expansion causes the copper slag to automatically pulverize. Figure 2 , Figure 3As shown, 90% of the particle size of the self-pulverized copper slag is concentrated below 30 microns, which meets the particle size requirement of about 200 mesh (74um) for magnetite magnetic separation, and cleverly solves the technical problems of long production lines and high energy consumption that cannot be avoided in common technologies such as crushing and grinding.

[0054] In comparison, in the commonly used technology, the copper slag after slow cooling needs to be ground and crushed to reach the particle size threshold of 200 mesh required for magnetic separation; firstly, the grinding and crushing steps have high energy consumption and low energy utilization rate, resulting in lengthy production lines and high costs; secondly, the grinding products of 200 mesh particle size level sometimes cannot achieve monomer dissociation, and some copper plants will grind to 325 mesh.

[0055] The composition of the self-pulverizing copper slag includes magnetite and gamma-type dicalcium silicate.

[0056] Based on the aforementioned regulation of the composition point of the mixed copper slag, the composition point of the mixed copper slag is located in the primary crystallization zone of dicalcium silicate. During the slow cooling process, dicalcium silicate is preferentially precipitated, and the liquidus iron content is controlled to be above 90%. During the slow cooling process, the copper mineral particles aggregate and grow, and the monomer dissociation degree of magnetite is significantly improved, which is conducive to the effective separation of magnetite in the subsequent magnetic separation process, and further improves the iron recovery rate.

[0057] Exemplarily, the cooling rate of the modified copper slag may be 0.25-0.5° C. / min.

[0058] S4. performing magnetic separation on the self-pulverized copper slag to recover magnetite.

[0059] In some embodiments, the particle size of the self-pulverized copper slag is 1 to 100 microns.

[0060] like Figure 1 As shown, in some embodiments, the particle size of the self-pulverizing copper slag is 1-60 um, wherein 90% of the copper slag particle size is concentrated below 30 um.

[0061] It can be seen that the particle size of self-pulverized copper slag can be directly used for magnetite collection in the magnetic separation process.

[0062] It should be noted that in the commonly used technology, the copper slag usually needs to be crushed and ground to less than 200 mesh before magnetic separation to achieve the monomer dissociation effect.

[0063] In some embodiments, in the step of magnetically separating the self-pulverized copper slag to recover magnetite, the intensity of the magnetic separation is 0.05-0.10T.

[0064] In order to facilitate those skilled in the art to further understand the present invention, examples are given below:

[0065] Example 1

[0066] A method for extracting iron by self-pulverization after phase reconstruction of copper slag, comprising the following steps:

[0067] The copper smelting slag was subjected to chemical phase analysis, and it was determined that the mass content of fayalite in the copper smelting slag was 15.37%, the mass content of magnetite was 20.59%, and the total iron content was 39.64%; a CaO-based additive was added to the copper smelting slag to obtain a mixed copper slag; the type of the calcium oxide-based additive was CaCO3, and the amount of CaCO3 added was 10% of the mass of the copper slag, and the amount of calcium oxide in the calcium carbonate was about 5.6% of the mass of the copper slag;

[0068] The mixed copper slag is heated to 1400°C and kept at this temperature for 60 minutes to obtain modified copper slag, wherein the modified copper slag comprises magnetite and β-C2S.

[0069] The modified copper slag is slowly cooled at a rate of 1°C / min. After the slow cooling, all β-C2S is converted into γ-C2S, and the volume expands by about 10%. The powdered copper slag is obtained. The actual picture of the powdered copper slag is as follows: Figure 2 As shown in Figure 2, the particle size distribution of self-pulverized copper slag is as follows: Figure 3 As shown, more than 95% of the particle sizes of the self-pulverized copper slag are below 325 meshes, the magnetite content in the self-pulverized copper slag is 34.12%, and nearly 90% of the iron in the fayalite is contained in the magnetite.

[0070] The self-pulverized copper slag was subjected to magnetic separation with a magnetic separation intensity of 0.08T and an iron recovery rate of up to 95%.

[0071] Example 2

[0072] A method for extracting iron by self-pulverization after phase reconstruction of copper slag, comprising the following steps:

[0073] The copper tailings were subjected to chemical phase analysis, and it was determined that the mass content of fayalite in the copper tailings was 18.54%, the mass content of magnetite was 24.87%, and the total iron content was 46.2%. A CaO-based additive was added to the copper tailings to obtain a mixed copper slag, the type of the calcium oxide-based additive was CaO, and the amount of CaO added was 6.5% of the mass of the copper slag.

[0074] The mixed copper slag is heated to 1600°C and kept at this temperature for 80 minutes to obtain modified copper slag. The product after the mineral phase reconstruction of the modified copper slag is magnetite and β-C2S.

[0075] The modified copper slag is slowly cooled at a rate of 0.5°C / min. After the slow cooling, all β-C2S is converted into γ-C2S, and the volume expands by about 10%, thereby obtaining self-pulverized copper slag. The content of magnetite in the self-pulverized copper slag is 42%, and nearly 95% of the iron in fayalite is contained in the magnetite. More than 95% of the particle size of the self-pulverized copper slag is below 350 mesh.

[0076] The self-pulverized copper slag was magnetically separated with a magnetic separation intensity of 0.06T and an iron recovery rate of 94%.

[0077] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for extracting iron from copper slag by self-pulverization, characterized in that: Includes steps: Mixing copper slag and a calcium oxide-based additive to obtain a mixed copper slag, wherein the calcium oxide-based additive includes calcium oxide and / or the calcium oxide raw material, the calcium oxide raw material can generate calcium oxide by heating, and the amount of the calcium oxide-based additive added satisfies that the total mass of the native calcium oxide and / or the generated calcium oxide is 29% to 47% of the mass of the fayalite phase in the copper slag; The mixed copper slag is heated to 1250° C. to 1700° C. and kept warm for 30 to 120 minutes to obtain modified copper slag; The modified copper slag is slowly cooled to room temperature at a cooling rate of 0.25-1°C / min to obtain the pulverized copper slag; The self-pulverized copper slag is subjected to magnetic separation to recover magnetite.

2. The method for extracting iron from copper slag by self-pulverization according to claim 1, characterized in that: In terms of mass fraction, the mass fraction of the fayalite phase in the copper slag is 10% to 40%.

3. The method for extracting iron from copper slag by self-pulverization according to claim 1, characterized in that: The particle size of the self-pulverizing copper slag is 1 to 100 microns.

4. The method for extracting iron from copper slag by self-pulverization according to claim 1, characterized in that: The particle size of the self-pulverizing copper slag is 1-60 um, wherein 90% of the copper slag particle sizes are concentrated below 30 um.

5. The method for extracting iron from copper slag by self-pulverization according to claim 1, characterized in that: The modified copper slag comprises magnetite and beta-dicalcium silicate.

6. The method for extracting iron from copper slag by self-pulverization according to claim 5, characterized in that: The self-pulverizing copper slag comprises magnetite and gamma dicalcium silicate.

7. The method for extracting iron from copper slag by self-pulverization according to claim 1, characterized in that: The calcium oxide raw material includes calcium carbonate and / or calcium sulfate.

8. The method for extracting iron from copper slag by self-pulverization according to claim 7, characterized in that: When the calcium oxide-based additive is calcium oxide, the heating temperature is 1400-1700°C; when the calcium oxide-based additive is calcium carbonate / calcium sulfate, the heating temperature is 1250-1700°C.

9. The method for extracting iron from copper slag by self-pulverization according to claim 1, characterized in that: In the step of magnetically separating the self-pulverized copper slag to recover magnetite, the magnetic field intensity of the magnetic separation is 0.05-0.10T.

10. Use of the method for extracting iron from copper slag by self-pulverization according to any one of claims 1 to 9 in copper slag treatment.

Citation Information

Cited By

  • Method for efficiently extracting iron from copper slag through non-molten hydrogen reduction

    CN121109739A

  • Method for inhibiting generation of liquid phase in fayalite type slag reduction roasting product

    CN121992188A